Keragaan Kartakter Kualitatif Generasi M1 Kedelai Varietas Dega 1 Hasil Radiasi Sinar Gamma - Octavia, Rini; Rasyad, Aslim; Isnaini, Isnaini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
The objective of this research aims to determine phenotypic performance and variability of M1 generation of Dega 1 soybean variety after irradiated seed by gamma ray radiation and get suitable rate of the mutagen to obtain genetic variability. Irradiation by gamma ray to the seed of Dega 1was established in the Laboratory of Badan Tenaga Atom Nasional, Jakarta while phenotypic observation was conducted in the Experimental Garden, Faculty of Agriculture, University of Riau beginning on January until April 2018 by using a completely randomized design. The treatments wereG1(50 Gy), G2 (100 Gy), G3(150 Gy) and G4(200 Gy) gamma ray radiation and parental line as a control. The characters observed were growth habits, leaflet number, leaf shape, flower crown color and pod color. Result of the research showed that gamma ray irradiation to the seed caused some levels of mutation on qualitative characters including, the change in leaflets number, and leaf shape but not for flower color and pod color.Â Irradiation seed by gamma rayÂ causedwide variability on leaf shape for all rates of irradiation with the coefficient of variation (CV) of ranging from 0.43 to 0.64. This inferred that the values of population variability of M1 resulted from seed irradiation was not similar in magnitude.Keywords:Soybean, qualitative characters, variability, gamma ray